A higher mortality in men compared to women with heart failure in primary care and ejection fraction equal to or more than 40% - Björn Eriksson; Per Wändell; Ulf Dahlström; Per Näsman; Lars H. Lund; Magnus Edner (Critical Public Health)
The aim of this study was to describe gender-related differences in characteristics and mortality in heart failure (HF) patients managed in primary care (PC). We included 1802 hF patients aged 77.5 ± 8.8 years (47% women) with ejection fraction (EF) ≥ 40% from the Swedish Heart Failure (SwedeHF) registry. The patients were divided by gender, and by heart failure with mildly reduced ejection fraction (HFmrEF; EF 40–49%) or heart failure with preserved ejection fraction (HFpEF; EF ≥ 50%). Men included in the study were younger (mean-age 76.4 vs 78.7 years, p < 0.0001) and showed a higher age-adjusted mortality (p < 0.0001). Men more often showed ischemic heart disease, 49% vs. 38% (p < 0.0001), atrial fibrillation, 56% vs. 50%, and diabetes, 25% vs. 17% (both p < 0.01). Women had higher blood pressure compared to men (p < 0.01), more commonly had kidney dysfunction (p < 0.01), and a worse functional capacity (p < 0.01). Cardiovascular diseases were the dominating causes of death in men and women (60% and 56%) but were less dominating in individuals with EF ≥ 50%, especially among women (56% in men vs. 46% in women). Among women with EF ≥ 50%, the mortality was dominated of mixed and unspecified diseases. Other important causes of death were cancer (15%) and chronic obstructive pulmonary disease (13%). Men managed in PC with HF and EF ≥ 40% have a higher age-adjusted mortality than women. Cardiovascular disease is the dominating cause of death in both genders. Other frequent causes of death were malignant tumors and respiratory diseases, illustrating the need to carefully diagnose and treat all associated comorbidities.